The unauthorized guide to iPhone, iPad, and iPod repair a DIY guide to extending the life of your iDevices! - Warner, Timothy L. (Que, 2013)
DON'T JUNK IT, FIX IT--AND SAVE A FORTUNE! The only reference & tutorial of its kind--in full color! Fix your own iPhone, iPad, or iPod with secret repair knowledge Apple doesn't want you to have! This groundbreaking, full-color book shows you how to resurrect expensive Apple mobile iDevices you thought were dead for good, and save a fortune. Apple Certified Repair Technician Timothy L. Warner demystifies everything about iDevice repair, presenting simple, step-by-step procedures and hundreds of crisp, detailed, full-color photos. He'll walk you through safely taking apart your iDevice, replacing what's broken, and reliably reassembling it. You'll learn where to get the tools and exactly how to use them. Warner even reveals sources for broken Apple devices you can fix at low cost--for yourself, or even for resale! Replace All These iDevice Components: Battery; Display; SIM card; Logic board; Dock connector. Take Apart, Fix, and Reassemble: iPod nano (5th & 7th Gen); iPod touch (4th & 5th Gen); iPhone (3GS, 4, 4S, & 5); iPad (iPad 2, iPad 4th Gen, & iPad mini). Fix Common Software-Related Failures: Emergency data recovery; Jailbreaking; Carrier unlocking. Do What Apple Never Intended: Resurrect a waterlogged iDevice; Prepare an iDevice for resale; Install non-Apple Store apps; Perform out-of-warranty repairs. All technical content reviewed & approved by iFixit, world leader in iDevice parts, tools, and repair tutorials!
Print version record
Keywords: iPhone (Smartphone) -- Maintenance and repair; iPad (Computer) -- Maintenance and repair; iPod (Digital music player) -- Maintenance and repair; iPhone (Téléphone intelligent); Entretien et réparations; iPad (Ordinateur); Entretien et réparations; iPod (Lecteurs de musique numérique); Entretien et réparations; Electrical & Computer Engineering; Engineering & Applied Sciences; Electrical Engineering